The Mutational Landscape of Pancreatic and Liver Cancers, as Represented by Circulating Tumor DNA - Rice, Alistair; del Rio Hernandez, Armando (Frontiers in Oncology, 2019)
The mutational landscapes of pancreatic and liver cancer share many common genetic alterations which drive cancer progression. However, these mutations do not occur in all cases of these diseases, and this tumoural heterogeneity impedes diagnosis, prognosis and therapeutic development. One minimally invasive method for the evaluation of tumour mutations is the analysis of circulating tumour DNA (ctDNA), released through apoptosis, necrosis and active secretion by tumour cells into various body fluids. By observing mutations in those genes which promote transformation by controlling the cell cycle and oncogenic signalling pathways, a representation of the mutational profile of the tumour is revealed. The analysis of ctDNA is a promising technique for investigating these two gastrointestinal cancers, as many studies have reported on the accuracy of ctDNA assessment for diagnosis and prognosis using a variety of techniques.